Relasi Prinsip Tauhid dalam Ekonomi Islam terhadap Pemikiran Etika Murthada Muthahari - Nugraha Hasan (IAIN Manado, 2019)
Ethics is an interesting discussion because the principle recognizes ethical values, such as fairness and honesty. Ethics give instructions to humans how to do good and avoid the bad. This research is a type of qualitative research and includes literature studies using literature, in the form of books, articles, and the results of previous research. Data obtained through literature review are direct and indirect quotations. Human ego which cannot be controlled will damage the value system that God has created. God created man to carry out the task of khalifah on earth. Where humans must protect and prosper the earth. So in running the wheel of the human economy must pay attention to all aspects so as not to conflict with Islamic values. All forms of cheating or fraud and negative actions are strictly prohibited in Islamic economics. This is an important point of the caliph's principle, which apply Islamic values in the running of the economy for human life. The results of this paper state that tauhidad is the root of the moral principles of the faithful that cannot be uprooted by any power. When the feeling of the subconscious turns into conscious, then all human actions can be categorized as moral deeds. That is what is reflected in the person of the holy men.